Novel bifunctional peptidic aspartic protease inhibitor inhibits chitinase A from Serratia marcescens: kinetic analysis of inhibition and binding affinity - Kumar, Ajit; Rao, Mala (Biochimica Et Biophysica Acta-General Subjects, 2010)
Background: Chitinase inhibitors have chemotherapeutic potential as fungicides, pesticides and antiasthmatics. The majority of chitinase inhibitors reported are natural products like argifin, argifin linear fragments, argadin, allosamidin and disulfide-cyclized peptides. Here, we report a novel peptidic inhibitor API (Aspartic Protease Inhibitor), isolated from Bacillus licheniforrnis that inhibits chitinase A (ChiA) from Serratia marcescens. Methods: The binding affinity of API with ChiA and type of inhibition was determined by the inhibition kinetics assays. Fluorescence and CD spectroscopic analysis and chemical modification of API with different affinity reagents elucidated the mechanism of binding of API with ChiA. Results and conclusions: The peptide has an amino acid sequence N-Ile(1)-Cys(2)-Glu(3)-Ala(4)-Glu(5)-His(6)-Lys(7)-Trp(8)-Gly(9)-Asp(10) -Tyr(11)-Leu(12)-Asp(13)-C. The ChiA-API kinetic interactions reveal noncompetitive, irreversible and tight binding nature of API with I-50= 600 nM and K-i = 510 nM in the presence of chromogenic substrate pnitrophenyl-N,N'-diacetyl-beta-chitobioside[p-NP-(GIcNAc)(2)]. The inhibition progress curves show a two-step slow tight binding inhibition mechanism with the rate constant k(5) = 8.7 +/- 1 x 10(-3) s(-1) and k(6) = 7.3 +/- 0.6 x 10(-5) s(-1). CD-spectra and tryptophanyl fluorescence analysis of ChiA incubated with increasing API concentrations confirms conformational changes in enzyme structure which may be due to irreversible denaturation of enzyme upon binding of API. Chemical modifications by WRK abolished the anti-chitinase activity of API and revealed the involvement of carboxyl groups in the enzyme inactivation. Abolished isoindole fluorescence of OPTA-labeled ChiA demonstrates the irreversible denaturation of ChiA upon incubation with API for prolonged time and distortion of active site of the enzyme. General significance: The data provide useful information that could lead to the generation of drug-like, natural product-based chitinase inhibitors. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; Chitinase A; Enzyme kinetics; Slow tight binding inhibition

Mechanistic insights into the inhibition of endo-beta 1,4 xyloglucan hydrolase by a classical aspartic protease inhibitor - Menon, Vishnu; Rao, Mala (Journal of Fluorescence, 2013)
This is the first report of inactivation of xyloglucanase from Thermomonospora sp by pepstatin A, a specific inhibitor towards aspartic proteases. The steady state kinetics revealed a reversible, competitive, two-step inhibition mechanism with IC (50) and K (i) values of 3.5 +/- 0.5 mu M and 1.25 +/- 0.5 mu M respectively. The rate constants determined for the isomerization of EI to EI* and the dissociation of EI* were 14.5 +/- 1.5 x 10(-5) s(-1) and 2.85 +/- 1.2 x 10(-8) s(-1) respectively, whereas the overall inhibition constant K (i) (*) was 27 +/- 1 nM. The conformational changes induced upon inhibitor binding to xyloglucanase were monitored by fluorescence analysis and the rate constants derived were in agreement with the kinetic data. The abolished isoindole fluorescence of o-phthalaldehyde (OPTA)-labeled xyloglucanase and far UV analysis suggested that pepstatin binds to the active site of the enzyme. Our results revealed that the inactivation of xyloglucanase is due to the interference in the electronic microenvironment and disruption of the hydrogen-bonding network between the essential histidine and other residues involved in catalysis.
Keywords: 4 xyloglucan hydrolase; Endo-beta 1; Enzyme kinetics; Inactivation mechanism; Pepstatin; Slow-tight binding

Biochemical characterization of recombinant mevalonate kinase from Bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Sonawane, Prashant; Shakeel Abbassi; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate kinase (MK; ATP: mevalonate 5-phosphotransferase; EC 2.7.1.36) plays a key role in isoprenoid biosynthetic pathway in plants. MK catalyzes the phosphorylation of mevalonate to form mevalonate-5-phosphate. The recombinant BmMK was cloned and over-expressed in E. coli BL21 (DE3), and purified to homogeneity by affinity chromatography followed by gel filtration. Optimum pH and temperature for forward reaction was found to be 7.0 and 30 degrees C, respectively. The enzyme was most stable at pH 8 at 25 degrees C with deactivation rate constant (Kd*) 1.398 x 10(-4) and half life (t(1/2)) 49 h. pH activity profile of BmMK indicates the involvement of carboxylate ion, histidine, lysine, arginine or aspartic acid at the active site of enzyme. Activity of recombinant BmMK was confirmed by phosphorylation of RS-mevalonate in the presence of Mg2+, having K-m and V-max 331.9 mu M and 719.1 pKat mu g(-1), respectively. The values of k(cat) and k(cat)/K-m for RS-mevalonate were determined to be 143.82 s(-1) and 0.43332 M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found 150.9 s(-1) and 1.023 M-1 s(-1). The metal ion studies suggested that BmMK is a metal dependent enzyme and highly active in the presence of MgCl2. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bacopa monniera; Enzyme kinetics; Mevalonate kinase; stability

Penicillin V acylase from pectobacterium atrosepticum exhibits high specific activity and unique kinetics - Avinash, Vellore Sunder; Ramasamy, Sureshkumar; Suresh, C. G.; Pundle, Archana (International Journal of Biological Macromolecules, 2015)
Penicillin V acylases (PVAs, E.C.3.5.11) belong to the Ntn hydrolase super family of enzymes that catalyze the deacylation of the side chain from phenoxymethyl penicillin (penicillin V). Penicillin acylases find use in the pharmaceutical industry for the production of semi-synthetic antibiotics. PVAs employ the N-terminal cysteine residue as catalytic nucleophile and are structurally and evolutionarily related to bile salt hydrolases (BSHs). Here, we report the cloning and characterization of a PVA enzyme from the Gram-negative plant pathogen, Pectobacterium atrosepticum (PaPVA). The enzyme was cloned and expressed in Escherichia coli attaining a very high yield (250 mg/l) and a comparatively high specific activity (430 IU/mg). The enzyme showed marginally better pH and thermo-stability over PVAs characterized from Gram-positive bacteria. The enzyme also showed enhanced activity in presence of organic solvents and detergents. The enzyme kinetics turned out to be significantly different from that of previously reported PVAs, displaying positive cooperativity and substrate inhibition. The presence of bile salts had a modulating effect on PaPVA activity. Sequence analysis and characterization reveal the distinctive nature of these enzymes and underscore the need to study PVAs from Gram-negative bacteria. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cooperative; Enzyme kinetics; Gram-negative; Penicillin V acylase; Substrate inhibition

Highly active bile salt hydrolase from enterococcus faecalis shows positive cooperative kinetics - Chand, Deepak; Ramasamy, Sureshkumar; Suresh, C. G. (Process Biochemistry, 2016)
Bile salt hydrolase (BSH; cholylglycine hydrolase, EC 3.5.1.24) is an important enzyme that catalyses the deconjugation of bile acids conjugated with glycine or taurine and assists in the reduction of blood cholesterol levels. In the present study, we report the cloning, overexpression and characterisation of BSH gene from a gut-associated microbe Enterococcus faecalis (EfBSH). The overexpressed protein in Escherichia coli was purified to homogeneity. Optimum pH and temperature for activity were found to be 5.0 and 50 degrees C, respectively. The enzyme was considerably stable in the pH range of 5.0-7.0 and at a temperature of up to 50 degrees C. It showed high specific activity of 1390 U mg(-1) and 1289 U mg-1 for substrates such as glycocholic acid (GCA) and glycodeoxycholic acid (GDCA), respectively. The effect of additives on enzyme activity was assessed, and the detergent Triton X showed a marginally enhanced activity. The enzyme demonstrated unique enzyme kinetics of non-linear regression, thereby displaying positive cooperativity. In addition, the modulating effect of the non-substrate ligand Pen V on the hydrolysing ability of EfBSH towards bile acid such as GDCA was measured. It was observed that Pen V significantly enhanced the BSH activity. This is markedly different from the previously reported competitive inhibition of BSH activity by Pen V. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Allosteric regulation; Bile acids; Bile salt hydrolase; Enzyme kinetics; Gut organism; Penicillin V acylase